HUBUNGAN LAMA WAKTU MENDERITA STROKE DENGAN TINGKAT KEMANDIRIAN KLIEN DALAM MELAKUKAN AKTIVITAS PEMENUHAN KEBUTUHAN SEHARI-HARI - Budi, Setia; Syahfitri, Ria Dila (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2018)
The rate of stroke incidence is about 200 per 100,000 people throughout the world. This study aims to determine the Relation Suffer Stroke With Independence Level In Neurology Polyclinic TK II DR Ak Gani Palembang Year Hospital 2017. The research method used is descriptive quantitative with cross sectional design that is done by interviewing techniques with questionnaires on 42 respondents with Accidental sampling technique. This research was conducted in August 2017. Data analysis used is univariate data analysis and bivariate data analysis with one way anova test result. The results of univariate analysis showed that the duration of the respondents suffering from stroke was between 2.10 years to 3.38 years. Also found that most respondents were at the level of independence f; independent, except bathing, dressing, moving, and one other function with a total of 12 respondents. The results showed that there was a significant relationship between the long suffering stroke with the level of independence with the value of p value 0.025. For that the need for rehabilitation to patients and families of patients in order to help improve the independence of stroke patients in doing their daily activities. Keywords         : Long Suffer Stroke, Level of Independence